ANDERSON ON VULNERABILITY. Issue 1 (3rd March 2020) - Assiter, Alison
Abstract: Recently, feminists have begun to draw attention to the vulnerability of human beings. This theoretical perspective lies in contrast to an element of the philosophical tradition that values autonomy and freedom. I would like, in this paper, to engage with some of the work of the feminist philosopher Pamela Anderson on the notion of vulnerability. I think that Anderson's recognition of vulnerability is important but I'd like to suggest a different way of thinking about this issue from Pamela's. I think there are more difficulties than Anderson recognizes with Kant's view of autonomy. Anderson argues that Kant's theory can be adapted to cover the relationality of human beings with each other. However, I don't think that this can be done without distorting Kant. Linked to this, she suggests that feminists ought to take into account existing "narrative identities." However, these existing "narrative identities" may be detrimental to their interests. Subjects may be "constituted" by injurious social norms. It seems to me that there is an ontological and normative dimension of the problem that is insufficiently articulated in Pamela's account. Kant's view of autonomy leaves no room for vulnerability in the sense of relationality. Drawing on Simone de Beauvoir I would like to suggest a different concept of freedom and autonomy from that of Kant that allows for vulnerability. De Beauvoir argues that the freedom of each of us requires the freedom of others. Additionally I will suggest that de Beauvoir offers an account of the conditions for the removal of oppression, including the elimination of ethically detrimental aspects of vulnerability.